2019
DOI: 10.1038/s41529-018-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of young cement water on the corrosion of the International Simple Glass

Abstract: Understanding the corrosion of nuclear waste glass is critical to predicting its safe disposal within a geological facility. The corrosion mechanisms and kinetics of the International Simple Glass, a simplified version of high-level nuclear waste glass, was shown to be significantly influenced by a high pH cement solution representative of disposal conditions. We provide the first microscopic characterisation of the porous, Zr-rich aluminoalkali-silica gel corrosion layer that was observed. Ca, Na and K from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
(86 reference statements)
2
21
3
Order By: Relevance
“…Molecular dynamics and Monte Carlo simulations are promising means to decipher the structure and properties of nanoporous networks 20,[49][50][51] , but more work is needed to parameterize laws for reactive transport models. Furthermore, although we have focused on a simple glass that does not form secondary silicate minerals, borosilicate nuclear waste glasses are known to form phyllosilicates, calcium silicate hydrates, and/or zeolites as corrosion products [52][53][54][55][56] . The precipitation of these minerals disrupts the passivating layer [57][58][59] .…”
mentioning
confidence: 99%
“…Molecular dynamics and Monte Carlo simulations are promising means to decipher the structure and properties of nanoporous networks 20,[49][50][51] , but more work is needed to parameterize laws for reactive transport models. Furthermore, although we have focused on a simple glass that does not form secondary silicate minerals, borosilicate nuclear waste glasses are known to form phyllosilicates, calcium silicate hydrates, and/or zeolites as corrosion products [52][53][54][55][56] . The precipitation of these minerals disrupts the passivating layer [57][58][59] .…”
mentioning
confidence: 99%
“…The pH of this young cement water is approximately 13.5. [21,22] Considering briefly the anticipated corrosion products, under anoxic conditions, magnetite, Fe(OH) 2 and FeOOH − have been suggested by the Pourbaix diagram, with latter being indicative of active corrosion. [23] The evolution of the surface environment is dependent upon the nature of the test cell.…”
Section: Grouted Steelmentioning
confidence: 99%
“…In the case of the Belgian Supercontainer and the U.K. disposal concepts for the storage of high- and intermediate-level vitrified wastes, the presence of cement is expected to play a significant role. Specific studies on the effect of Ordinary Portland Cement or portlandite on the dissolution behavior of high- or intermediate-level vitrified wastes have been conducted in Belgium (Supercontainer design), the U.K. (colocation of different waste types), and France (intermediate-level vitrified wastes) [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microscopically, the formation of a complex SAL has been identified as a prerequisite for the slower dissolution kinetics of stage II. In many cases, electron microscopy revealed that the SAL consists of a silica-based layer made of aggregated colloids and sometimes exhibits a layered structure [ 9 , 12 , 13 ]. Different glass dissolution models explaining the mechanism of the SAL formation and the rate-limiting steps have been proposed and are still under debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation